Enhancing counseling teachers’ creativity through Deep Counseling-based Training - Eka Sakti Yudha; Ahman; Agus Taufiq; Dian Munawarah; Kania Cahyaningtyas; Moch. Dendi Arief Prawira; Muzayyinah Al-Usrah; Yalda Suvita (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
This community service program aimed to enhance the creativity of guidance and counseling teachers through deep counseling-based training. The training was conducted on July 10, 2025, involving 49 guidance and counseling teachers from junior and senior high schools. Using the Participatory Action Research (PAR) method, the program included pre-test, panel discussion on deep counseling, innovation showcase, practical sessions, and post-test. Results showed a positive impact on teachers' creativity, with participants in the "balanced creativity" category increasing from 85.7 percent in the pre-test to 91.8 percent in the post-test. This improvement demonstrates that the training effectively enhanced teachers' ability to balance creative exploration with professional consistency in delivering counseling services. The integration of creative media into deep counseling encouraged teachers to design innovative, contextual, and student-centered services. This activity contributed to strengthening guidance and counseling teachers' competence to provide more effective, engaging, and sustainable counseling services that respond to students' psychosocial needs. The program also serves as a model for continuous professional development that can be replicated in other regions, focusing on the integration of digital technology, diversification of counseling media, and enhancement of competencies in addressing the complexity of contemporary student issues.